PBPK Modeling of the Effect of Reduced Kidney Function on the Pharmacokinetics of Drugs Excreted Renally by Organic Anion Transporters. Issue 3 (24th July 2017) - Hsueh, C‐H; Hsu, V; Zhao, P; Zhang, L; Giacomini, KM; Huang, S‐M
Abstract : Altered pharmacokinetics (PK) in subjects with chronic kidney disease (CKD) may lead to dosing adjustment of certain drugs in subjects with CKD. It can be valuable to quantitatively predict PK in CKD for the management of drug dosing in these subjects. We developed physiologically based pharmacokinetic (PBPK) models of seven renally eliminated drugs: adefovir, avibactam, entecavir, famotidine, ganciclovir, oseltamivir carboxylate, and sitagliptin. These drugs are all substrates of renal organic anion transporters (OATs). Drug models verified using PK data from healthy subjects (HS) were coupled with physiological models representing CKD that incorporated prior knowledge of effects of CKD on hepatic and renal elimination. The models reasonably described clinically observed PK changes in subjects with CKD (compared to subjects with normal renal function), with predicted AUC changes within 50% of the observed changes. PBPK models can be used to prospectively predict PK of renally eliminated OAT substrates in subjects with CKD.